Pelaksanaan Audit Internal Pada Masa Pandemi COVID-19 Studi - Nurlinda Nurlinda; Vivianti Novita; Junus Sinuraya (Jurnal Riset Akuntansi dan Bisnis, 2022)
This study aims to analyze the implementation of online higher education internal quality audits during the COVID-19 pandemic. This research is a qualitative research using case studies. Collecting data by conducting observations and in-depth studies on the implementation of the 2021 Internal Quality Audit at Politeknik Negeri Medan. Data analysis used descriptive analysis. The results of the study found that, during the COVID-19 pandemic, internal quality audits could be carried out using a combination of online and offline Medan State Polytechnic, utilizing the Google Drive facility for document audits and face-to-face (offline) for field audits